The Influence of The Existence of Farmers' Groups on The Development of Community Empowerment in Agriculture in Kampung Beringin Baru, Jorong Makmur, Padang Gelugur District - Winda Safitri; Syur'aini Syur'aini (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This research is motivated by the many problems experienced by members of farmer groups. This is characterized by the still low income from harvests from farmer groups, resulting in their lives being less prosperous. Therefore, according to researchers, it is very suitable for holding community empowerment in Beringin Baru village, Jorong Makmu, Padang Gelugur sub-district in the agricultural sector. Based on the geographical location of Beringin Baru village, Jorong Makmu, Padang Gelugur sub-district which is in a water area where the land for rice fields is still very large, therefore, according to the author, a farmer group program in the form of community empowerment is very suitable to be carried out. The type of research is literature study research, with research techniques using interview/observation techniques. The research results show that 1) There are many problems faced by new banyan farmer groups related to their agriculture. 2) The influence of the existence of farmer groups in Beringin Baru is not very significant in increasing the potential of the farming community, so that the community does not understand and understand the problems they are facing. 3) Based on the problems and influence of the new banyan farmer group, there is a great need for a community empowerment program in the agricultural sector that can boost agricultural development in the new banyan village, both in terms of human resources, natural resources, and the harvests that will be obtained by the farming community.